Biaxial tensile behavior and strength of architectural fabric membranes. (February 2020) - Shi, Taibai; Hu, Jianhui; Chen, Wujun; Gao, Chengjun
Abstract: The utilization of composite fabric membrane materials for large-span membrane structures has attracted considerable attention in recent decades due to enhanced material properties. Biaxial mechanical properties with respect to real engineering applications are essential and indispensable in comparison with uniaxial ones. This study focuses on true biaxial characteristics of a typical polyvinylidene fluoride (PVDF)-coated polyester membrane material in terms of stress-strain characteristics and breaking criteria. The true stress-strain curves obtained from an experimental study, i.e. seven loading ratios on the basis of symmetry and typical conditions, are investigated with digital image correlation method. The interpolation of these curves in combination of least square method achieves a three-dimensional strain surface as a function of warp and weft strains, which is useful to assess reasonable structural behavior. A new breaking criteria intended for architectural fabric membrane is proposed in analogy to Tsai-Hill, Yeh-Stratton and Norris failure criteria. The basic constants in the criteria are determined using experimental results. A comparative analysis between available uniaxial and biaxial criteria shows that the new criteria can cover all criteria due to the fact that biaxial mechanical properties are larger than uniaxial ones. Furthermore, a similar but glued specimen is employed to compare welded specimens. It is obtained that observations, values and curve tendency are similar, demonstrating the suitability of using new specimens to identify true biaxial properties. Highlights: Achieve 3D strain surfaces and biaxial stress-strain equations. Propose a breaking criteria for fabric membrane and determine constants. Validate the suitability of new specimens to identify biaxial properties.